Pengaruh Kualitas Produk, Harga Dan Varian Produk Terhadap Keputusan Pembelian Produk Daging Segar - Karimi Karimi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
This study aims to determine the effect of product quality, price and product variants on the decision to purchase fresh meat at the bestmeat shop. The sample used in this study was 100 bestmeet store customers. The method in this research is a quantitative method. The results showed that partially or simultaneously product quality, price and product variants have an effect on fresh meat buying decisions. Based on the test results Fcount 50.762 > Ftable 2.70, it can be concluded that the variable product quality, price and product variant simultaneously influence the decision making of purchasing fresh meat products at the BestMeat Bireuen Store.